Natural History of Preoperative Subcentimeter Pulmonary Nodules in Patients With Resectable Pancreatic Adenocarcinoma. Issue 5 (May 2015) - Chang, Stephanie T.; Nguyen, Dennis C.; Raptis, Constantine; Menias, Christine O.; Zhou, Gongfu; Wang-Gillam, Andrea; Linehan, David C.; Hawkins, William G.; Strasberg, Steven M.; Fields, Ryan C.
<x xml:space="preserve">Abstract</x> Objective: To determine the detection rate, radiologic characteristics, and natural history of incidental subcentimeter pulmonary nodules (SCPN) among patients with resectable pancreatic adenocarcinoma and to clarify whether further preoperative evaluation should be considered. Background: The clinical significance of SCPN detected by routine preoperative abdominal imaging in patients with pancreatic adenocarcinoma is unknown. Methods: Patients who underwent resection for pancreatic adenocarcinoma between 2000 and 2010 were queried from a prospectively maintained database at a single institution. Pre- and postoperative computed tomographic (CT) imaging was independently reviewed and the presence and radiologic features of SCPNs were analyzed for associations with overall survival (OS). Results: Of the 463 patients who met inclusion criteria, 329 (71%) had reviewable preoperative imaging. Preoperative SCPNs were described in 59 patients (18%), and 41 patients had follow-up imaging available for review. Only increasing age (67.1 vs 63.5 years; P = 0.005) was associated with the presence of SCPN. Six patients (1.8%) had new or enlarging nodules after surgery, of whom 5 (1.5%) had confirmed metastatic adenocarcinoma. There was no difference in OS between patients with or without preoperative SCPN (16.1 vs 19.1 months; P = 0.201). No radiographic criterion of SCPN (including number, size, laterality, calcification, or contour) was associated with OS. Conclusions: Neither the presence of preoperative SCPN nor nodule characteristics was associated with OS among patients who underwent pancreaticoduodenectomy (PD) for pancreatic cancer. These data do not support routine additional workup of preoperative SCPN in patients with resectable pancreatic adenocarcinoma.